2011
DOI: 10.1016/j.canlet.2011.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of microRNA expression in tamoxifen-sensitive MCF-7 versus tamoxifen-resistant LY2 human breast cancer cells

Abstract: Microarrays identified miRNAs differentially expressed and 4-hydroxytamoxifen (4-OHT) regulated in MCF-7 endocrine- sensitive versus resistant LY2 human breast cancer cells. 97 miRNAs were differentially expressed in MCF-7 versus LY2 cells. Opposite expression of miRs- 10a, 21, 22, 29a, 93, 125b, 181, 200a, 200b, 200c, 205, and 222 was confirmed. Bioinformatic analyses to impute the biological significance of these miRNAs identified 36 predicted gene targets from those regulated by 4-OHT in MCF-7 cells. Agreem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 77 publications
6
63
0
Order By: Relevance
“…2). In a microarray-based study on tamoxifen-sensitive MCF-7 and tamoxifen-resistant LY2 breast cancer cell lines, several novel miRNAs including miR-200c were found to be differentially expressed between sensitive and resistant cells [65]. In a later study by the same group, it has been shown that ectopic expression of miR-200c in endocrine-resistant LY2 cells has significant effect on enhanced sensitivity to fulvestrant, but not to tamoxifen [66].…”
Section: Mir-200c and Targeted Therapy Resistancementioning
confidence: 92%
“…2). In a microarray-based study on tamoxifen-sensitive MCF-7 and tamoxifen-resistant LY2 breast cancer cell lines, several novel miRNAs including miR-200c were found to be differentially expressed between sensitive and resistant cells [65]. In a later study by the same group, it has been shown that ectopic expression of miR-200c in endocrine-resistant LY2 cells has significant effect on enhanced sensitivity to fulvestrant, but not to tamoxifen [66].…”
Section: Mir-200c and Targeted Therapy Resistancementioning
confidence: 92%
“…Since miRNAs were first discovered, they have been identified as significant mediators in cellular physiology and pathology. Recently, studies have demonstrated that aberrant miRNA expression is strongly linked with tumor-related processes in humans (Fassan et al, 2011;Li et al, 2011;Manavalan et al, 2011;Matsuyama et al, 2011). Moreover, miRNAs appear to be potent regulators of gene expression in endometriosis and its associated reproductive disorders, raising the prospect of using miRNAs as biomarkers and therapeutic tools in endometriosis (Teague et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to ERa, there is a plasma membrane-bound estrogen receptor that is a G-coupled protein receptor (GPR30IGPER) [11,12]. Filardo et al have shown that E2 can activate the MAPK signaling cascade via binding to GPR30 leading to transcription of cell proliferative genes [13] .…”
Section: Gpr30/ Gpermentioning
confidence: 99%